2000
DOI: 10.1038/sj.jea.7500102
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire and hair measurement of exposure to tobacco smoke

Abstract: To assess the relation between nicotine and cotinine levels in hair and reported exposure to environmental tobacco smoke ( ETS ) , hair samples from 112 children ( aged 3 months to 10 years ) and 76 of their mothers were analyzed and information on the smoking habits of household adults in the preceding 6 months recorded. It was found that the levels of nicotine in children's hair were related to the number of smokers in the house, and increased with the total number of cigarettes smoked by all household adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
(50 reference statements)
2
42
3
Order By: Relevance
“…2,10,[18][19][20] Hair-nicotine concentrations among the children in this study were higher than those in other studies reporting hair-nicotine concentrations in young children. The median level of hair nicotine found in children in this present study (1.7 ng/mg; IQR: 0.3-4.2) is higher than was found by Al-Delaimy et al 21 23 Because all of the child participants in this present study were <5 years of age, it is unlikely that personal tobacco use, either smoked or smokeless, significantly contributed to hair nicotine concentrations. However, the case may be that thirdhand tobacco smoke, or airborne nicotine that has settled and been ingested orally through hand-to-mouth behavior in young children or through dermal absorption, may contribute to exposure.…”
Section: Discussioncontrasting
confidence: 53%
“…2,10,[18][19][20] Hair-nicotine concentrations among the children in this study were higher than those in other studies reporting hair-nicotine concentrations in young children. The median level of hair nicotine found in children in this present study (1.7 ng/mg; IQR: 0.3-4.2) is higher than was found by Al-Delaimy et al 21 23 Because all of the child participants in this present study were <5 years of age, it is unlikely that personal tobacco use, either smoked or smokeless, significantly contributed to hair nicotine concentrations. However, the case may be that thirdhand tobacco smoke, or airborne nicotine that has settled and been ingested orally through hand-to-mouth behavior in young children or through dermal absorption, may contribute to exposure.…”
Section: Discussioncontrasting
confidence: 53%
“…Figure 5 suggests a positive association between hair nicotine concentrations and the number of cigarettes smoked in a household. Other studies have reported a similar concentration range and exposure-response relationships of hair nicotine concentration of children with the number of cigarette smoked per day by other household members (Al-Delaimy et al, 2000;Sorensen et al, 2007). Al-Delaimy et al (2000) reported that median hair nicotine concentrations from children who were exposed to SHS from 0 (n = 24), 1-9 (n = 23), 10-19 (n = 31) and 20 or more (n = 34) cigarettes smoked per day by household adults were 0.001, 0.1, 0.22 and 2.4 ng/mg, respectively (estimated from Fig.…”
Section: Analysis Of Field Hair Samplesmentioning
confidence: 67%
“…Evaluating the magnitude of SHS exposure and identifying its sources are fundamental steps needed to reduce exposure and to target prevention strategies. SHS exposure is assessed by diverse methods, including questionnaires (Al-Delaimy et al, 2000;Delfino et al, 1993;Gaffney et al, 2003;Klepeis, 1999), air nicotine monitoring (Hammond and Leaderer, 1987;Leaderer, 1990;Navas-Acien et al, 2006;Repace et al, 2006;Wipfli et al, 2008), and biomonitoring of nicotine or cotinine in such biofluids as serum, urine or saliva (Benowitz, 1999;Coultas et al, 1987;Seccareccia et al, 2003;Pirkle et al, 2006). The most commonly used biomarker for SHS exposure is nicotine or its metabolite, cotinine, in human body fluids such as urine, saliva and serum (Pichini et al, 2000;Simoni et al, 2006;Thaqi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This measure provides a long-term (months) evaluation of smoke exposure since the nicotine in the bloodstream of hair follicle capillaries is incorporated in the growing hair shaft ( Al-Delaimy, 2002 ;Al-Delaimy, Crane, & Woodward, 2000 ). The half-life of nicotine in body fl uids is approximately 2 -3 h r and that of cotinine (a major nicotine metabolite) is 1 -2 days ( Benowitz, 1996 ).…”
Section: Hair Nicotinementioning
confidence: 99%